Analisis Kepuasan Pasien Rawat Jalan Berdasarkan Tingkat Kepentingan dan Kinerja Layanan di Puskesmas Ngaglik 1, Sleman, D.I. Yogyakarta: Indonesia - Wijayanti, Punik Mumpuni; Suryaningsih, Betty Ekawati; Kurnia, Arif Rahmat; Nugroho, Adi (UII, 2024)
Background: Puskesmas is the spearhead of health services in Indonesia. In order to improve its services to the community, Puskesmas (public health center) must continuously increase their performances. Budget constraints make puskesmas must make improvements according to priority scale. Puskesmas have difficulty to determine priority as expected by society. Objective: This study aims to analyze the satisfaction of the Puskesmas visitors based on the level of performance and the level of importance which is then prioritized in accordance with the service attribute. Method: This research use cross sectional method with simple random sampling at Ngaglik 1 Sleman Yogyakarta Public Health Center visitors. Data were collected by using questionnaire based on likert scale with measured parameters including tangible, reliability, responsiveness, assurance and empathy. Data processing uses the method of Important Performance Analysis (IPA) and Potential Gain in Customer Value (PGCV). Data sufficiency uses a 10% accuracy rate, a 90% confidence rate, and a margin of error of 0.1 (10%). The subjects involved were 45 patients who were present at the Ngaglik Community Health Center at the time the research took place Results: Satisfaction analysis shows that the level of respondent satisfaction is spread so uneven in every service attribute. Values ​​for attributes considered to be important by the respondents averaged 3.14 while the average performance score of 4.18. There are different priorities that need to be improved according to IPA and PGCV. The five priorities that have to be fixed by IPA are the bathroom facilities, the speed and accuracy of the service of the officer, the completeness and the sophistication of medical equipment, drug security, and timeliness of service, while according to PGCV is the right JKN card service, knowledge and job mastery of the officers, completeness and sophistication of medical equipment, fast service when visitors arrive, and administrative length. Conclusion: The priority of service improvement according to IPA and PGCV differs from one to another. In general, researchers recommend the use of IPA method because this method saves time and cost. In general, puskesmas should improve services to match the expectations of visitors.